Does age of patient impact the outcome of tympanoplasty? A study in a tertiary care center - Jaiswani, Geetanjali; Kumar, Rajesh; Chakraborty, Priyanko (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic suppurative otitis media (CSOM) is one of the most common cause of reversible conductive hearing loss in world especially in countries with poor socio-economic status, poor nutritional habits, hygiene and lack of health education. It affects both sexes and all age groups. Successful outcome of tympanoplasty depends on various factors. Methods: This study was conducted to evaluate impact of age on outcome of type 1 tympanoplasty. Cases were selected, after proper history taking and preoperative evaluations, type 1 tympanoplasty was conducted under local anesthesia with temporalis fascia graft using underlay technique through post-auricular approach. Patients were followed up in postoperative period for 6 months. Results: Best results were observed in age group of 21-40 years and poorer outcomes were seen in patients more than 40 years and those less than 20 years age. Conclusions: The outcome of type 1 tympanoplasty is affected by age of patient.